PENGEMBANGAN OBJEK WISATA AIR TERJUN JERO KERTI BERBASIS EKOWISATA DI DESA DASAN GERIA KEC. LINGSAR KABUPATEN LOMBOK BARAT - Laksana, Dewa Gde Ari; Rahmatin, Baiq Anggita Arsya; Mardianto, Muhammad Ilham; Shofiana, Shofiana; Mantika, Annisa; Hairunnisa, Saskia Anggun; Aprilia, Rizka; Wangi, Minatul; Yulianingsih, Heni; Indrawan, I Nyoman Gde Ary; Putri, Dinda Marlia Putr; Putri, Dinda Marlia (Jurnal Wicara, 2024)
Dasan Geria Village is a village in Lingsar District, West Lombok Regency which has potential as a tourist village because it has a variety of tourist attractions. One of the tourist attractions is the very beautiful Jero Kerti waterfall. From the beauty of the Jero Kerti waterfall tourist attraction, there are several challenges faced, namely the lack or limitations of development of the tourist attraction, difficult road access, lack of awareness of local residents regarding efforts to maintain the sustainability and naturalness of the tourist attraction, as well as efforts to legalize the tourist attraction. To overcome these challenges, an ecotourism-based tourist attraction development program was held by the PMD - UNRAM 2024 KKN group, with the aim of empowering the community in managing sustainable tourist attractions through socialization activities, observing tourist attractions, making guidebooks and workshops on ecotourism. held on 2 July – 22 August 2024 in Dasan Geria Village. This program has produced results in the form of increased awareness and knowledge of the community or their desire to be involved in the programs offered. To start efforts to develop tourist attractions based on Jero Kerti waterfall ecotourism, an MOU letter was prepared as a first step. Not only that, to increase the success of the program, tourist attraction guidebooks, leaflets and news newspapers and maps were created with the aim of being promotional media